Exploration design of maternal and child hospital with biophilic architecture approach - Iis Purwati; Ai Siti Munawaroh (Program Studi Arsitektur Fakultas Sains dan Teknik (F-INTEN), 2023)
West Lampung Regency is divided into 15 sub-districts with an area of 2,064 km2. West Lampung Regency only has 1 special hospital with a population of 304,874 residents and 86,761 families. The hospital is located in the city of Liwa, which is at the western end of West Lampung Regency. This makes it difficult for the community to access the reach of health services, especially when mothers give birth or check for pregnancy and child health due to the location of the hospital which is quite far from several sub-districts located at the eastern end of West Lampung. The distance from the sub-district which is at the easternmost tip to the hospital is 51.7 km, this will certainly be a problem for maternal and child health insurance in West Lampung. Based on these problems, the application of the required design is a design that can also be a therapeutic tool that can help the patient's healing process. Biophilic architecture is an alternative approach that can solve this problem. The purpose of this study is to apply the concept of biophilic architecture to maternal and child hospitals in West Lampung Regency.